The Targeted Therapies for Osteosarcoma via Six Major Pathways - Wang, Shuxing; Ren, Quanlei; Li, Guoqing; Zhao, Xiaoxuan; Zhao, Xing; Zhang, Zhen (Current Molecular Pharmacology, 2024)
Osteosarcoma is the most common primary bone malignancy and has a high tendency of local invasion. Although a lot of studies have focused on chemotherapy and combination chemotherapy regimens in recent years, still, there is no particularly perfect regimen for the treatment of relapsed or metastatic OS, and the prognosis is still relatively poor. As a new therapeutic method, targeted therapy provides a new scheme for patients with osteosarcoma and has a wide application prospect. This article reviews the latest progress of targeted therapy for osteosarcoma, and summarizes the research on the corresponding targets of osteosarcoma through six major pathways. These studies can pave the way for new treatments for osteosarcoma patients who need them.
Keywords: CCNE1/CDK2